Relationship between Consumer Expenditures and Savings: The Contribution of Survey Research - Katona, George; Likert, Rensis (The Review of Economics and Statistics, 1946)
George Katona, Rensis Likert, Relationship between Consumer Expenditures and Savings: The Contribution of Survey Research, The Review of Economics and Statistics, Vol. 28, No. 4 (Nov., 1946), pp. 197-199